2006
DOI: 10.1105/tpc.106.041277
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisABA INSENSITIVE4 Regulates Lipid Mobilization in the Embryo and Reveals Repression of Seed Germination by the Endosperm

Abstract: Regulation of seed germination requires coordinate action by the embryo and surrounding endosperm. We used Arabidopsis thaliana to establish the relative roles of embryo and endosperm in the control of seed germination and seedling establishment. We previously showed that endospermic oil reserves are used postgerminatively via gluconeogenesis to fuel seedling establishment and that lipid breakdown is repressed by abscisic acid (ABA) in embryo but not endosperm tissues. Here, we use RNA amplification to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
333
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(360 citation statements)
references
References 52 publications
(73 reference statements)
24
333
3
Order By: Relevance
“…The transcription factors ABI3, ABI4, and ABI5 are well known positive regulators of the ABA responses during seed germination (Finkelstein and Lynch, 2000;Lopez-Molina et al, 2002;Penfield et al, 2006). Our study showed that the expression levels of ABI3, ABI4, and ABI5 were significantly increased in the cer9 mutant.…”
Section: Gene Identifiersupporting
confidence: 50%
See 2 more Smart Citations
“…The transcription factors ABI3, ABI4, and ABI5 are well known positive regulators of the ABA responses during seed germination (Finkelstein and Lynch, 2000;Lopez-Molina et al, 2002;Penfield et al, 2006). Our study showed that the expression levels of ABI3, ABI4, and ABI5 were significantly increased in the cer9 mutant.…”
Section: Gene Identifiersupporting
confidence: 50%
“…We also noted changes in the levels for proteins involved in lipid metabolism. Lipid is an important storage reserve, providing energy for radicle protrusion and seedling growth, and lipid mobilization is affected by ABA treatment during seed germination (Penfield et al, 2006). Previous reports indicate that oleosin proteins are involved in seed germination, enlargement of intracellular oil bodies, and total lipid and protein accumulation (Siloto et al, 2006;Shimada et al, 2008).…”
Section: An Isobaric Tags For Relative and Absolute Quantitation Expementioning
confidence: 99%
See 1 more Smart Citation
“…ABI4 encodes an Activator Protein-2/Ethylene-Responsive Factor transcription factor that binds the CE1-like element (CACCG) present in many ABA-and sugarresponsive promoters (Finkelstein et al, 1998;Niu et al, 2002;Acevedo-Hernández et al, 2005). ABI4 is a crucial determinant of ABA sensitivity during TAG breakdown in the embryo (Penfield et al, 2006). ABI3 and ABI5, which encode B3 and basic-region Leu zipper-type transcription factors, respectively, participate in the repression of TAG degradation by close association with the N-end rule components PRT6 and ATE (Holman et al, 2009).…”
mentioning
confidence: 99%
“…In particular, the transcription factors ABI3, ABI4, and ABI5 enhance sensitivity to ABA (12). ABI3 has been shown to act upstream of ABI5 (16), and ABI4 has been implicated in the repression of seedling lipid degradation (17). The mechanisms through which ABA desensitization occurs are not well understood.…”
mentioning
confidence: 99%